Communicating Microbiology Results. It's Not Just What You Say, But How You Say It. (4th October 2017) - Musgrove, Mary; Kenney, Rachel M; Kendall, Ronald; Tibbetts, Robert; Samuel, Linoj; Peters, Mike; Davis, Susan
Abstract: Background: Gaps in microbiology communication can lead to suboptimal antibiotic prescribing. In May 2016, our laboratory modified reporting of respiratory cultures growing commensal flora only to specify "no methicillin-resistant Staphylococcus aureus /MRSA or Pseudomonas aeruginosa " (PA). The purpose of this study was to compare MRSA and PA antibiotic therapy utilization before and after the change. Methods: IRB approved, quasi-experiment at four hospitals with an antimicrobial stewardship program. Dates: August 1, 2015–January 31, 2016 and August 1, 2016–January 31, 2017. Included: ≥18 years, commensal flora only respiratory culture, empiric MRSA and PA antibiotic for treatment of lower respiratory infection. Excluded: non-respiratory infection. Primary outcome: MRSA or PA therapy de-escalated. Secondary outcomes: time to culture result, MRSA and PA antibiotic days of therapy, length of stay. Safety outcomes: acute kidney injury (AKI), C. difficile (CDI), subsequent multi-drug-resistant organism (MDRO), in-hospital all-cause mortality. Results: Two hundred and ten patients included, 105 per group. Median age 64 and 61 years, male sex 52% and 56% in pre- and post-group, respectively. Empiric antibiotics, pre vs. post: vancomycin 94% vs. 95%; cefepime 66% vs. 36%; piperacillin–tazobactam 10% vs. 46%. MRSA or PA antibiotics de-escalated: 39% pre and 73% post ( P  < 0.001). See Table 1 for variables associated with antibiotic de-escalation. Days of therapy: 7 vs. 5 days ( P  < 0.001). AKI 31% vs. 14% ( P  = 0.003). Eight subsequent MDRO in pre and one in post ( P  = 0.035). No differences: time to culture result, length of stay, mortality,  CDI. Conclusion: Improved microbiology communication to assist prescriber interpretation of commensal respiratory flora was associated with a reduction in the proportion of patients that received antibiotics targeting MRSA and PA. Disclosures: S. Davis, Merck: Received grant through college that I'm faculty for, Grant recipient; Allergan: Speaker's Bureau, Consulting fee; Allergan: Consultant and Scientific Advisor, Consulting fee; Medicines Company: Consultant and Scientific Advisor, Consulting fee; Zavante: Consultant and Scientific Advisor, Consulting fee.